Teaching first order phase transition using a zipper model - Perayil, Reshma; Murkoth, Udayanandan Kandoth; Pulinchery, Prasanth (Momentum: Physics Education Journal, 2022)
In 1968, Kittel published the zipper model for demonstrating the first order phase transition which is applicable to DNA like structures. This paper utilize this model to explain the behavior of many thermodynamic properties before, at and after phase transition to get a clear picture about what the changes are happening to the system during phase transition. Many textbooks say that entropy and volume show discontinuity at phase transition whereas Gibbs free energy is continuous. The zipper model shows that energy is also discontinuous as shown in the paper. Understanding the phase transition is still a difficult topic for the undergraduate students and hopefully this paper can help them to overcome this difficulty.